Effect of commercial fibrolytic enzymes application to normal- and slightly lower energy diets on lactational performance, digestibility and plasma nutrients in high-producing dairy cows - Yang, Jiahua; Zhao, Shengguo; Lin, Bo (Frontiers in Veterinary Science, 2024)
The inclusion of fibrolytic enzymes in the diet is believed to have positive effects on animal production. Hence, the objective of this study was to investigate the impact of supplementing diets with a commercial fibrolytic enzyme preparation (Vistamax; mixture of xylanase and cellulase) derived from Trichoderma reesei on lactational performance, digestibility, and plasma nutrient levels in high-producing dairy cows. Two dietary energy levels were considered: a normal energy diet (metabolizable energy = 2.68 Mcal/kg) and a slightly lower energy diet (metabolizable energy = 2.55 Mcal/kg). A total of 120 lactating Holstein cows (parity = 2; Days in Milk = 113±23) were randomly assigned to four treatment groups using a 2 * 2 factorial arrangement. The dietary treatments consisted of: 1) normal energy diet without enzyme supplementation (NL); 2) normal energy diet with enzyme supplementation (NLE); 3) slightly lower energy diet without enzyme supplementation (SL); and 4) slightly lower energy diet with enzyme supplementation (SLE). The amount of enzyme added to the diets was determined based on previous in vitro studies and supplier recommendations. The enzyme and premix were mixed prior to the preparation of the total mixed ration, and the trial lasted for a duration of 42 days. The results indicated that the application of the fibrolytic enzyme did not have a significant effect on dry matter intake (DMI), but it did enhance the digestibility of dry matter (DM), neutral detergent fiber (NDF), potentially digestible NDF (pdNDF), organic matter (OM), milk production, milk urea nitrogen (MUN), and blood urea nitrogen (BUN). On the other hand, the slightly lower energy diet resulted in a decrease in DMI, milk production, milk protein yield, plasma free amino acids (FAA), and an increase in plasma B-hydroxybutyrate (BHBA). In conclusion, the inclusion of the fibrolytic enzyme in the diets of dairy cows led to improvements in the digestibility of DM, NDF, pdNDF, OM, milk production, and feed efficiency. Furthermore, the application of the enzyme to the slightly lower energy diet resulted in milk production levels comparable to those observed in cows fed the untreated normal energy diet.